A litván-lengyel-fehérorosz etnikai kontaktzóna megjelenése az első világháború előtti térképeken - Németh, Ádám (Közép-Európai Közlemények, 2014)
The aim of this paper is to analyze the emergence and evolution of the Lithuanian – Polish – Belarusian ethnic contact zone on the ethnographic maps from the middle of the 19th century until World War I. In case of the so called ‘Vilnius region’ the high level of ethnic, linguistic and religious diversity, the inaccurate statistical data, the extremely difficult question of identity formation and various ideological trends also resulted in a strange phenomenon: the distances between ethnographic boundaries depicted by different cartographers of the 19–20th centuries became huge: in particular cases ca. 100–150 km. The most important scientific result of this paper is the mapping – as layers with modern GIS methods – of former ethnographic borders of various maps edited by various (Russian, Belarusian, Polish, Lithuanian) cartographers. By the example of the ‘Vilnius region’ the study draws attention to the significance of source-critical analysis of historical thematic maps and the problems and limits of researches focusing on sharp ethnic boundaries.